2010
DOI: 10.1111/j.1439-0264.2010.01024.x
|View full text |Cite
|
Sign up to set email alerts
|

Regional Distribution and Relative Frequency of Gastrointestinal Endocrine Cells in the ddN Mice: An Immunohistochemical Study

Abstract: The distributions and frequencies of some endocrine cells in the eight portions of the gastrointestinal (GI) tract - fundus, pylorus, duodenum, jejunum, ileum, cecum, colon and rectum of the ddN mouse, were studied with immunohistochemical method using seven types of antisera against chromogranin (Cg) A serotonin, somatostatin, glucagon, gastrin, cholecystokinin (CCK)-8 and human pancreatic polypeptide (hPP). In the GI tract of ddN mice, CgA, serotonin, somatostatin, glucagon, gastrin, CCK-8 immunoreactive (IR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…In the present study, SOM-14-IR cells were observed throughout the whole intestinal tract except for the large intestines of mole-rats. These results correlated with those of some rodent studies (Sandstrom & El-Salhy 2000;Ku et al 2003;Sarı et al 2007) but were quite different from those conducted on mice strains and porcupine (Ku et al 2004b(Ku et al , 2006Yaman et al 2007;Lee et al 2010).…”
Section: Duodenumsupporting
confidence: 81%
See 3 more Smart Citations
“…In the present study, SOM-14-IR cells were observed throughout the whole intestinal tract except for the large intestines of mole-rats. These results correlated with those of some rodent studies (Sandstrom & El-Salhy 2000;Ku et al 2003;Sarı et al 2007) but were quite different from those conducted on mice strains and porcupine (Ku et al 2004b(Ku et al , 2006Yaman et al 2007;Lee et al 2010).…”
Section: Duodenumsupporting
confidence: 81%
“…species and within parts of the gastrointestinal tracts. In addition, many studies have elucidated the regional distributions and relative frequencies of different endocrine cells in the gastrointestinal tracts of various vertebrates, including various species of rodents (Ku et al 2004a(Ku et al , 2004bYaman et al 2007;Lee et al 2010). The present study identified the existence and distributions of neuropeptide-secreting endocrine cells in the small and large intestines of mole-rats.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cells or fibres comprising >30% of the immunoreactivity for each antiserum compared with intact dermal keratinocytes or dermal tissue were regarded as positive, and the mean numbers of caspase‐3, PARP, NT and 4‐HNE‐immunoreactive epithelial cells (%, cells/100 epithelial cells) were counted using an established automated image analysis process , with some modifications. Additionally, the percentages occupied by MMP‐9 immunoreactive fibres in the dermis were calculated (%/mm 2 dermis).…”
Section: Methodsmentioning
confidence: 99%